Tråkigt på jobbet: Dokumentstyrning av revisorer och lärare - Jonnergård, Karin; Krantz, Joakim (Socialvetenskaplig tidskrift, 2018)
Bored at work – Auditors and teachers under management by documents The aim is to investigate how experiences of work amongst teachers and auditors change as a shift from input control towards action control is implemented through management by documents. The study is based on interviews with auditors and teachers with long professional experience. The result shows that action control of professionals implies that (i) the core of work shifts from being based on relationships with clients to be based on documentation; (ii) priorities change to satisfy document requirements; (iii) there is a reduction in the sense of the work being relevant. These implications reduce the professionals work-related enthusiasm. In conclusion: management by document establishes conditions that do not provide incentives for professionals to fully apply their individual capabilities, thereby also preventing professional development and learning.